2017
DOI: 10.2217/bem-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Reflex and Neural Tourniquet: Harnessing the Healing Power of the Vagus Nerve

Abstract: The CNS helps protect against tissue injury. The most important priorities include limiting blood loss and systemic inflammation. We elucidated two endogenous neural pathways that rapidly and specifically improve hemostasis and decrease inflammation through vagus nerve signaling. Activation of the neural tourniquet or inflammatory reflex via electrical vagus nerve stimulation (VNS) significantly improves outcomes in preclinical disease models. Currently, VNS is clinically approved for the treatment of medicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Typically, a reduced baroreflex FB gain and a depressed HRV, together with an elevated HR, are interpreted as signs of a depressed vagal activity at the heart level. These observations suggest a vagal driver for an effective resuscitation, and this hypothesis is in line with the recent literature on vagus nerve stimulation as an innovative therapeutic strategy, which has been proven to be beneficial also in septic shock (Borovikova et al, 2000;Tracey, 2002;Liu et al, 2006;Bansal et al, 2010;Czura et al, 2010;Huston and Fritz, 2018).…”
Section: Autonomic Dysfunction and Association With Vascular Changessupporting
confidence: 85%
“…Typically, a reduced baroreflex FB gain and a depressed HRV, together with an elevated HR, are interpreted as signs of a depressed vagal activity at the heart level. These observations suggest a vagal driver for an effective resuscitation, and this hypothesis is in line with the recent literature on vagus nerve stimulation as an innovative therapeutic strategy, which has been proven to be beneficial also in septic shock (Borovikova et al, 2000;Tracey, 2002;Liu et al, 2006;Bansal et al, 2010;Czura et al, 2010;Huston and Fritz, 2018).…”
Section: Autonomic Dysfunction and Association With Vascular Changessupporting
confidence: 85%
“…As final remark, innovative technologies in the field of bioelectronic medicine are growing and they are advocated as the future medicine for the vast majority of diseases. These techniques are based on the direct stimulation of the ANS, in particular of the vagus nerve and clinical trials are ongoing [44]. Our model could be used to evaluate the efficacy of such treatment on LV contractility and relating control mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Mental stress is also one of the causes of VVS. Studies showed that mental stress is a main cause of vagal reflex in patients undergoing vascular intervention [10]. PICC catheterization is an invasive operation on blood vessels and many patients suffer from mental stress because they have limited knowledge about the operation.…”
Section: Mental Stressmentioning
confidence: 99%